Developing Methodological Competence of Future Technology Teachers through Web Platforms - Mukimovna, Khamdamova Nozima (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
Modern promising scientific areas in the world are undoubtedly formed, developed and improved through the introduction of digital technologies into the educational process. This area includes the problems of intelligent educational systems, open education, distance learning, information educational environments. This area is closely related, on the one hand, to pedagogical and psychological problems, and on the other hand, to the results achieved in scientific and technical fields such as telecommunication technologies and networks, computer systems for information processing, visualization and interaction with people, artificial intelligence, automated systems for modelling complex processes and other results.One of the current issues is the study of the possibilities of using web platforms in the development of methodological competence of future technology teachers and the determination of the effectiveness of their implementation in practice. The main goal of this article is to analyse the possibilities of using modern web platforms to further improve the pedagogical competence of future teachers. This, in turn, will allow teachers to teach the most modern methods used to effectively organize lessons and encourage students to participate actively.